Association of ADIPOQ gene variants with body weight, type 2 diabetes and serum adiponectin concentrations: the Finnish Diabetes Prevention Study - Venojärvi Mika; Eriksson Johan G; Kolehmainen Marjukka; Lindström Jaana; Pulkkinen Leena; Siitonen Niina; Ilanne-Parikka Pirjo; Keinänen-Kiukaanniemi Sirkka; Tuomilehto Jaakko; Uusitupa Matti (BMC, 2011)
Abstract Background Adiponectin, secreted mainly by mature adipocytes, is a protein with insulin-sensitising and anti-atherogenic effects. Human adiponectin is encoded by the ADIPOQ gene on the chromosomal locus 3q27. Variations in ADIPOQ are associated with obesity, type 2 diabetes (T2DM) and related phenotypes in several populations. Our aim was to study the association of the ADIPOQ variations with body weight, serum adiponectin concentrations and conversion to T2DM in overweight subjects with impaired glucose tolerance. Moreover, we investigated whether ADIPOQ gene variants modify the effect of lifestyle changes on these traits. Methods Participants in the Finnish Diabetes Prevention Study were randomly assigned to a lifestyle intervention group or a control group. Those whose DNA was available (n = 507) were genotyped for ten ADIPOQ single nucleotide polymorphisms (SNPs). Associations between SNPs and baseline body weight and serum adiponectin concentrations were analysed using the univariate analysis of variance. The 4-year longitudinal weight data were analysed using linear mixed models analysis and the change in serum adiponectin from baseline to year four was analysed using Kruskal-Wallis test. In addition, the association of SNPs with the risk of developing T2DM during the follow-up of 0-11 (mean 6.34) years was analysed by Cox regression analysis. Results rs266729, rs16861205, rs1501299, rs3821799 and rs6773957 associated significantly (p < 0.05) with body weight at baseline and in the longitudinal analyses. The rs266729 C allele and the rare minor alleles of rs2241766 and rs2082940 were associated with an increased adjusted hazard ratio of developing T2DM. The differences in baseline serum adiponectin concentrations were seen according to rs16861210, rs17366568, rs2241766, rs6773957 and rs2082940 and differences in the change of serum adiponectin levels from baseline to the four year examination were seen according to rs16861205, especially in subjects who were able to lose weight during the first year of intervention. Conclusions These results from the Finnish Diabetes Prevention Study support the concept that genetic variation in ADIPOQ locus contributes to variation in body size and serum adiponectin concentrations and may also modify the risk of developing T2DM. Trial registration number ClinicalTrials.gov NCT00518167